PENGGUNAAN GRAMATIKA DALAM TAJUK RENCANA PADA KORAN RADAR SULTENG - Hojianto, Hojianto (BAHASANTODEA, 2015)
The problem in this research is grammar usage in editorial on  Radar Sulteng newspaper. The purpose of this research is to describe the grammar usage in editorial on Radar Sulteng newspaper. The kind of this research is quatitative research with describing data with detail. Research with taking an object using  the Radar Sulteng newspaper is bassed on data accumulation with carefully. According to this reaserch is do with collect data written  in crown draft. After the research  is done to get crops as such as grammar usage that described accordance with the aspect of study the editorial of October 2014 edition that is spelling, morphology, and syntactic. The conclutions of this research is grammar usage in editorial on Radar Sulteng newspaper there is only a small part to error undersanding rule of indonesian language which appropiate with language standard system and perfect spelling. Keywords: grammar usage, in editorial.